Improving management of small-scale irrigation systems: a possible field of assistance for nongovernment organizations?: experiences from Hambantota District, Sri Lanka - Jungeling, I. (International Irrigation Management Institute, 1990)
Experiences from Hambantota District tank settlement project, Sri Lanka where the author did research on the contributions of a non-governmental organization in improving small-scale irrigation systems.